2015
DOI: 10.1093/jat/bkv036
|View full text |Cite
|
Sign up to set email alerts
|

Nefopam Hydrochloride: A Fatal Overdose

Abstract: Nefopam is a non-opiate analgesic commonly used for the treatment of moderate to severe pain. A case of a 37-year-old male who was found dead in the morning is presented. An autopsy was performed and femoral venous blood, heart blood, urine, and vitreous humor were submitted for toxicological analysis. A general drug screen detected the presence of nefopam, caffeine, nicotine, citalopram, gabapentin, amitriptyline, diazepam and paracetamol in cardiac blood. Nefopam was quantitated by high-performance liquid ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 21 publications
0
4
1
Order By: Relevance
“…No studies have yet been reported on the effect of acute toxic dose of Nefopam on this respect. However, this finding may be contrary to Moini et al that the proposed IL-1β can affect significantly after taking opioid or Nefopam (20)(21)(22)(23), but more research must be done.…”
Section: B-contrasting
confidence: 78%
See 2 more Smart Citations
“…No studies have yet been reported on the effect of acute toxic dose of Nefopam on this respect. However, this finding may be contrary to Moini et al that the proposed IL-1β can affect significantly after taking opioid or Nefopam (20)(21)(22)(23), but more research must be done.…”
Section: B-contrasting
confidence: 78%
“…The resulting supernatant was then directly fed into the HPLC, yielding 30 μl. Before HPLC analysis, the samples were not diluted (18,22).…”
Section: Collection and Preparation Of Liver Heart And Brain Tissues ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The death was attributed to atherosclerotic coronary artery disease and therapeutic drug toxicity. Citalopram was quantified at 0.7 mg/L and 0.9 mg/L in unpreserved femoral and cardiac blood, respectively, whereas acetaminophen concentrations were not provided [33]. Acetaminophen and citalopram are among the 10 most frequently detected drugs in hanging and drug poisoning (intoxication) suicides.…”
Section: Discussionmentioning
confidence: 99%
“…Nefopam is a benzoxazine that was developed in the 1960s as a muscle relaxant, but clinical use revealed that it has non-opioid, centrally acting, non-steroidal analgesic abilities, and it was used for relief of moderate pain (Seetohul et al, 2015). Its unique mode of action involves inhibition of the reuptake of serotonin, noradrenaline, and dopamine and may interact with the glutamatergic system (Saghaei et al, 2012).…”
Section: Introductionmentioning
confidence: 99%